Effects of exercise training on cardiovascular risk factors in kidney transplant recipients: a systematic review and meta-analysis - Chen, Gang (Ren Fail, 2019)
Background: Whether exercise can improve cardiovascular health in kidney transplant recipients (KTRs) is unclear. Therefore, we performed a systematic review of the effects of exercise on cardiovascular risk factors in this population setting. Methods: Randomized control trials (RCTs) evaluating the impact of exercise on major clinical outcomes in KTRs were identified by searches in Cochrane CENTRAL, PubMed, EMBASE, OVID and CBM updated to December 2018. The main outcomes of interest were blood pressure, lipid profile, blood glucose level, arterial stiffness, kidney function, body weight, body mass index, exercise tolerance (VO(2) peak) and quality of life (QOL). Results: After screening 445 studies in the database, we included 12 RCTs in the review and 11 RCTs for further qualitative analysis. The results indicate a significant improvement in small arterial stiffness [mean difference (MD): −1.14, 95% confidence interval (CI): −2.19–0.08, p = .03], VO(2) peak (MD: 2.25, 95% CI: 0.54–3.69, p = .01), and QOL (MD: 12.87, 95% CI: 6.80–18.94, p < .01) after exercise intervention in KTRs. However, there is no evidence for an improvement in blood pressure, lipid profile, blood glucose level, kidney function, body weight or body mass index. Conclusion: Exercise intervention in KTRs improves arterial stiffness but does not consistently contribute to the modification of other CVD risk factors like hypertension, dyslipidemia, hyperglycemia, decreased kidney function and obesity. Exercise also improves exercise tolerance and QOL in KTRs.